2018
DOI: 10.1007/s00402-018-2997-7
|View full text |Cite
|
Sign up to set email alerts
|

Force distribution of a cylindrical grip differs between dominant and nondominant hand in healthy subjects

Abstract: Percent contribution of the thumb and the fingers to total grip strength differed between dominant and nondominant hands with a change in distribution when assessing maximum grip force. In right-handed subjects, thumb and ring finger have important roles during gripping.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 31 publications
0
32
0
Order By: Relevance
“…The human hand has evolved [87] as a function of active constraints [88][89][90][91][92][93][94][95][96][97][98][99][100] and is in harmony with other sensory systems such as the visual and auditory brain [97,99,101]. Grip force profiles are a direct reflection of complex low-level, cognitive, and behavioral synergies this evolution has produced [87][88][89][90][91][92][93][94][95][96][97][98][99][100][101]. The state of the art in experimental studies on grip force control for lifting and manipulating objects [88,89,91,93,94] provides insight into the contributions of each finger to overall grip strength and fine grip force control.…”
Section: Seven Properties Of Self-organization In a Somatosensory Neumentioning
confidence: 99%
See 1 more Smart Citation
“…The human hand has evolved [87] as a function of active constraints [88][89][90][91][92][93][94][95][96][97][98][99][100] and is in harmony with other sensory systems such as the visual and auditory brain [97,99,101]. Grip force profiles are a direct reflection of complex low-level, cognitive, and behavioral synergies this evolution has produced [87][88][89][90][91][92][93][94][95][96][97][98][99][100][101]. The state of the art in experimental studies on grip force control for lifting and manipulating objects [88,89,91,93,94] provides insight into the contributions of each finger to overall grip strength and fine grip force control.…”
Section: Seven Properties Of Self-organization In a Somatosensory Neumentioning
confidence: 99%
“…Human grip force is governed by self-organizing prehensile synergies [91,92] that involve from-local-to-global functional interactions (property 6) between sensory (low-level) and central (high-level) representations in the somatosensory brain. Grip force can be stronger in the dominant hand compared with the non-dominant hand and may reverse spontaneously depending on the necessity for adaptive ability (property 3) as a function of specific environmental constraints [95,96,100]. In recent studies, the grip force profiles from thousands of force sensor measurements collected from specific locations on anatomically relevant finger parts on the dominant and non-dominant hands revealed spontaneous adaptive grip force changes in response to sensory stimuli [105], and long-term functional plasticity (property 5) as a function of task expertise [103,104].…”
Section: Seven Properties Of Self-organization In a Somatosensory Neumentioning
confidence: 99%
“…Studies have shown that hand gripping force and load distribution have a significant effect on the hand function. The importance of thumb, ring finger, and palms in determining the motion perception and the grip in the dominant hand was emphasized (6,7). In the literature, there are studies conducted with university students which suggest that somatosensory stimuli changes brain activation and long-term memory skills (8).…”
Section: Introductionmentioning
confidence: 99%
“…Obviously, there is need for data on literature which includes not only the use of upper extremity dominant side in healthy individuals depending on the parameters such as muscle and grip strength, age, height, BMI and gender but also vary from the reaction time to motion perception and distance determination in young adults according to auditory stimuli (6).…”
Section: Introductionmentioning
confidence: 99%
“…The dominant hand in general generates smaller force contributions of the thumb and the ring finger, and greater force contributions of the palm of the hand [10]. Left handers are less consistent compared to right handers in performing better with their dominant hands [11]. It is currently suggested that the right and left brain hemispheres may each represent the movements of the contralateral, not the ipsilateral hand, however, the programming of isometric fingertip forces is initially based on internal memory representations of physical device properties in addition to visual and haptic information from the current manipulations.…”
Section: Introductionmentioning
confidence: 99%